Salmonella type III effector SopB modulates host cell exocytosis - Charlotte A Perrett; Daoguo Zhou (Emerging Microbes and Infections)
Salmonella enterica pathogenesis is dependent on its ability to enter and replicate inside host cells. Replication occurs inside the Salmonella-containing vacuole (SCV), a vacuolar compartment that is modified by bacterial effectors secreted through the two type III secretion systems (T3SS-1 and T3SS-2). Type III effectors interact with the host cell endocytic pathway to aid replication. We investigated whether Salmonella effector proteins may also interact with the host’s exocytic pathway. A secreted alkaline phosphatase (SEAP) assay indicated three Salmonella effectors inhibited the secretory pathway, although only Salmonella outer protein B (SopB) was confirmed to block exocytosis using a vesicular stomatitis virus glycoprotein-green fluorescent protein (VSVG-GFP) transport assay. The 4-phosphatase activity of SopB was crucial to its effect on exocytosis. The interaction with the secretory pathway could potentially be important for providing replicating Salmonella with nutrients, contributing membrane material necessary for SCV biogenesis, altering antibacterial peptide/protein secretion or manipulating cell surface proteins important in the host response to infection.